Bintrafusp alfa, a bifunctional fusion protein targeting TGF-β and PD-L1, in advanced squamous cell carcinoma of the head and neck: results from a phase I cohort. Issue 2 (7th July 2020) - Cho, Byoung Chul; Daste, Amaury; Ravaud, Alain; Salas, Sébastien; Isambert, Nicolas; McClay, Edward; Awada, Ahmad; Borel, Christian; Ojalvo, Laureen S; Helwig, Christoph; Rolfe, P Alexander; Gulley, James L; et al.
Abstract : Background: We report the clinical activity and safety of bintrafusp alfa, a first-in-class bifunctional fusion protein composed of the extracellular domain of the transforming growth factor β (TGF-β)RII receptor (a TGF-β 'trap') fused to a human IgG1 monoclonal antibody blocking programmed death-ligand 1 (PD-L1), in patients with heavily pretreated squamous cell carcinoma of the head and neck (SCCHN). Methods: In this phase I dose-expansion cohort, patients with advanced SCCHN not amenable to curative therapy that progressed/recurred after platinum therapy in the recurrent/metastatic setting, or <6 months after platinum therapy in the locally advanced setting, received bintrafusp alfa 1200 mg intravenously every 2 weeks. The primary endpoint was confirmed best overall response (BOR; Response Evaluation Criteria for Solid Tumors (RECIST) 1.1) per independent review committee (IRC); other endpoints included BOR per investigator and safety. Results: As of August 24, 2018, 32 patients had received bintrafusp alfa (median follow-up 86.4 weeks; range 2–97). Per IRC, the confirmed objective response rate (ORR) was 13% (95% CI 4% to 29%; 4 partial responses (PR)); 4 patients had stable disease (SD) (disease control rate 25%; 95% CI 12% to 43%). Per investigator, there were 5 PRs (ORR, 16%), including 2 patients who developed delayed PRs after initial disease increase (total clinical response rate 22%). Responses (ORRs) were observed in patients with PD-L1-positive (12%), PD-L1-negative (17%; 73-10 antibody for immunohistochemistry), human papillomavirus (HPV)-positive (33%) and HPV-negative tumors (5%). Grade 3 treatment-related adverse events (TRAEs) were reported in 11 patients (34%), with no grade 4 TRAEs or treatment-related deaths. Conclusions: Bintrafusp alfa showed clinical activity across subgroups of PD-L1 expression and in HPV-positive tumors and had a manageable safety profile in patients with heavily pretreated advanced SCCHN. Activity in HPV-positive tumors is favorable compared with historical data from PD-L1 inhibitors and is being further investigated in an ongoing study of HPV-associated tumors. Trial registration number: NCT02517398 .